2005
DOI: 10.1111/j.1365-2125.2005.02322.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginkgo and ginger on the pharmacokinetics and pharmacodynamics of warfarin in healthy subjects

Abstract: AimThe aim of this study was to investigate the effect of two common herbal medicines, ginkgo and ginger, on the pharmacokinetics and pharmacodynamics of warfarin and the independent effect of these herbs on clotting status. MethodsThis was an open label, three-way crossover randomized study in 12 healthy male subjects, who received a single 25 mg dose of warfarin alone or after 7 days pretreatment with recommended doses of ginkgo or ginger from herbal medicine products of known quality. Dosing with ginkgo or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(159 citation statements)
references
References 35 publications
7
152
0
Order By: Relevance
“…Garlic was shown to be safe if carefully monitored, ginseng was shown to significantly increase the clearance/bioavailability of S-warfarin (data that gives cause for further studies), and ginkgo biloba was shown to present no significant health risk in the study group. However, further studies in the elderly were suggested (Candelario-Jalil et al, 2006;Jiang et al, 2005Jiang et al, , 2006Macan et al, 2006;Wolf, 2006).Where some studies and reports found a safety risk and some did not, all found the need for further development and research in the area of CAS-drug interactions (CambriaKiely, 2002;Candelario-Jalil et al, 2006;Jayasekera et al, 2005;Jiang et al, 2005Jiang et al, , 2006Kruth et al, 2004;Lesho et al, 2004;Macan et al, 2006;McClaskey & Michalets, 2007;Rozenfeld et al, 2004;Wolf, 2006).…”
Section: Possible Drug-cas Interactionsmentioning
confidence: 99%
“…Garlic was shown to be safe if carefully monitored, ginseng was shown to significantly increase the clearance/bioavailability of S-warfarin (data that gives cause for further studies), and ginkgo biloba was shown to present no significant health risk in the study group. However, further studies in the elderly were suggested (Candelario-Jalil et al, 2006;Jiang et al, 2005Jiang et al, , 2006Macan et al, 2006;Wolf, 2006).Where some studies and reports found a safety risk and some did not, all found the need for further development and research in the area of CAS-drug interactions (CambriaKiely, 2002;Candelario-Jalil et al, 2006;Jayasekera et al, 2005;Jiang et al, 2005Jiang et al, , 2006Kruth et al, 2004;Lesho et al, 2004;Macan et al, 2006;McClaskey & Michalets, 2007;Rozenfeld et al, 2004;Wolf, 2006).…”
Section: Possible Drug-cas Interactionsmentioning
confidence: 99%
“…93,94 Ang-Lee et al identified increased potential for bleeding with ginkgo extracts and recommended discontinuation 36 hours before surgery. 95 The American Society of Anesthesiologists recommends patients discontinue herbal medicines (including ginkgo) 2 weeks before elective surgery.…”
Section: Ginkgomentioning
confidence: 99%
“…Taste and aroma of ginger may be calming. Large doses of ginger have been shown to have antiplatelet activity [13].…”
Section: Gingermentioning
confidence: 99%
“…Large doses potentially harmful stomach pain, gas, vomiting, and inhibition of platelet formation [13].…”
Section: Garlicmentioning
confidence: 99%